New evidence from the Aketala site in the oasis of the Western Tarim Basin, Xinjiang for the prehistoric human-environment interaction - Wenli Zheng; Yuanjie Jiao; Mingmin Zhang; Xi He; Shuting Pu; Yonghao Guo; Zhengchuang Hui; Yanfang Pan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Last deglaciation to early Holocene vegetation and hydrology variations in the Middle Tianshan Mountains: a multi-proxy analysis of a lacustrine-peat sediment core from Chaiwopu Basin - Yunpeng Yang; Yangyang Zhang; Shuting Pu; Xiaona Zhang; Panjie Gong (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

pH/temperature dual-responsive antifungal delivery system based on polydopamine-modified montmorillonite for sustained essential oil release - Guixiang Teng; Hongyu Wang; Shuting Zhang; Mengyuan Yu; Yanzan Meng; Meng Zhao; Yan Yang; Peng Pu; Chun Zhang (Applied Clay Science, 2026)

The Heme Cavity Is Essential for the Peroxidase and Antibacterial Activity of Homodimer Hemoglobin from the Blood Clam Tegillarca granosa - Lili Pu; Shuting Dai; Zongming Wu; Sufang Wang; Yongbo Bao (Fishes, 2024)
This study investigates the essential role of the heme cavity in the peroxidase and antibacterial activities of homodimeric hemoglobin (Tg-HbI) from the blood clam Tegillarca granosa. After treatment with sodium dodecyl sulfate (SDS), the peroxidase and antibacterial activities of the Tg-HbI were significantly inhibited, with the degree of inhibition correlating positively with the SDS concentration. Fluorescence spectroscopy, UV-Vis spectroscopy, and molecular docking analysis further revealed that SDS interacts with key amino acid residues (e.g., His70 and His102) in the heme cavity of Tg-HbI, causing conformational changes that disrupt the internal hydrophobic interactions, thus inhibiting its function. This study confirms that the antibacterial effect of Tg-HbI is mediated through its peroxidase activity and that the heme cavity plays a critical role in maintaining this activity. These findings lay a foundation for further research on the immune defense functions of hemoglobin and provide new insights into the mechanisms of environmental adaptation in T. granosa.

Measuring and modeling the effects of green barriers on the spatial distribution of fine particulate matter at roadside - Xin Chen; Jie Wu; Wenbin Yang; Zhanyong Wang; Shuting Chen; Xisheng Hu; Kaifa Lu; Zhongmou Fan; Mei Lin; Pu Chen (Urban Climate, 2023)

A review of advanced oxidation process towards organic pollutants and its potential application in fracturing flowback fluid - Xing Li; Yang Bai; Xian Shi; Shuang Chang; Shuting Tian; Meiming He; Na Su; Pingya Luo; Wanfen Pu; Zhicheng Pan (Environmental Science and Pollution Research, 2023)

Effect of supply chain resilience on firm’s sustainable competitive advantage: a dynamic capability perspective - Guoli Pu; Shuting Li; Ju Bai (Environmental Science and Pollution Research, 2023)